Persisting Patronage: Challenges to Breaking Gender Barriers in Thai Elections - Aim Sinpeng (Journal of Current Southeast Asian Affairs)
The 2023 elections witnessed the highest number of women in national parliament in Thailand's history. What explains this sharp rise in women's political leadership in Thailand? Based on in-depth interviews with 18 women candidates and party executives across six political parties, this paper finds that party leadership and individual political entrepreneurship account for increased success rates of women candidates. Parties that adopt voluntary gender quota and champion diversity policies tend to have greater incentive to support women candidates to win. Yet, significant structural and institutional barriers remain, mostly notably the entrenched patronage system. Even in cases where there is strong party support for gender equity, male party leaders continue to dominate resources, networks and decisions regarding candidate selection. While the success of female MPs in the 2023 election provides promising evidence that the country is moving in the right direction toward greater female representation in parliament, major significant challenges remain.